Collaborative Project-Based Learning: An Alternative Program to Accommodate Students’ Active Learning in Speaking Class - Alviaderi Novianti; Susie Kusumayanthi (Universitas Batanghari Jambi, 2023)
This study was motivated by the difficulty of lecturer in inviting and motivating students to be actively involved in English Speaking class, students tend to be passive. There are some factors that might block them from speaking English in class. Many researches revealed that the main problem is psychological factor. Therefore, this study aimed at providing an insight and alternative program of students’ active learning that might be used and implemented by EFL lecturer, especially in English Speaking class. This study used Research and Development (R&D) with ADDIE (analyze, design, develop, implement, and evaluate) design. There were 53 students of higher education involved as research sample. They were selected using total sampling technique. The instrument used in this research were observation sheet and interview. the researchers could find that this collaborative project-based learning approach could facilitate the students to be actively involved in learning as well as give possitive impact to the students’ engagement in learning. They were given space to shout out their ideas, views, and voices comfortably. Students also considered that this approach was not only fun to do but also accustomed them to work together in group to produce something, be responsible, and think critically and creatively in solving the problems.